PERMOHONAN KELUAR ISLAM: KAJIAN KES DI MAHKAMAH TINGGI SYARIAH NEGERI SABAH: Application to Leave Islam: A Case Study in Sabah Shariah High Court - Pg Musa, Pg Ismail; Ismail, Siti Zubaidah (Jurnal Syariah, 2015)
In 2010, the Shariah Courts in Sabah have reportedly received 238 applications to leave Islam, the largest number in Malaysia. Out of this number, 67 applications have been approved. This has given rise to the question as to why these applications were done and how they were dealt with by the Shariah Courts in Sabah. The main objective of this article is to study how the Shariah Courts in Sabah handled those cases, by examining case files at two High Courts in Kota Kinabalu and Keningau. To achieve this objective, semi-structured interviews and observations were also conducted. Throughout the analysis, it is found that the majority of cases were identified as cases to certify the applicants’ religious status rather than application to convert out of Islam. This study also found that applications to convert out of Islam were also filed by non-Muslims and also by those whose religious status have not been determined due to mixed marriages between Muslim and non-Muslim. Apart from that, there were also cases filed by those who professed Islam in mass ceremonies in the 1970s until 1980s. Although this finding shows that the issue regarding apostasy in Sabah is not rampant, the Shariah Courts nevertheless, are required to adjudicate the cases. In the final part of this article, the writers give some recommendations regarding management approach and statutory amendment in order to improve the management of such cases in the Shariah Courts of Sabah.